New approaches to crop yield insurance in developing countries - Skees, Jerry; Hazell, Peter B. R.; Miranda, Mario (International Food Policy Research Institute, 1999)
Natural disasters can be extremely disruptive to farmers and to others whose incomes depend on a successful crop. Society can gain from more efficient sharing of crop and natural disaster risks. However, the costs associated with traditional agricultural risk programs have historically exceeded the gains from improved risk sharing. This paper explores government intervention in agricultural risk markets and discusses new approaches to risk sharing with limited government involvement. In particular, we build the case for introducing negotiable state-contingent contracts settled on area crop yield estimates or locally appropriate weather indices. These instruments could replace traditional crop insurance at a lower cost to government while meeting the risk management needs of a wider clientele.